2019
DOI: 10.1002/pon.5053
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and quality of life among Chinese American breast cancer survivors: The mediating role of self‐stigma, ambivalence over emotion expression, and intrusive thoughts

Abstract: Objectives: Highly acculturated Chinese American breast cancer survivors have greater access to health care providers, are English language proficient, and have more knowledge about the health care system. However, less is known about the potential psychosocial factors that may account for the health benefits of acculturation. As such, the current study seeks to understand how mainstream acculturation is associated with higher quality of life by investigating self-stigma, ambivalence over emotion expression (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…In our study, the mean score of self‐stigma was 18.57 (SD = 4.83), which is higher than that of Chinese–American breast cancer survivors with a self‐stigma being 16.30 (SD = 7.18; Tsai et al, 2019). When Chinese immigrants adapted and adjusted to mainstream American culture, they received social support such as the Pink Ribbon campaign to protect them from self‐stigma (Tsai et al, 2019). We also found that women who chose mastectomy without reconstruction reported significantly higher levels of self‐stigma than those who chose breast conservative surgery.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In our study, the mean score of self‐stigma was 18.57 (SD = 4.83), which is higher than that of Chinese–American breast cancer survivors with a self‐stigma being 16.30 (SD = 7.18; Tsai et al, 2019). When Chinese immigrants adapted and adjusted to mainstream American culture, they received social support such as the Pink Ribbon campaign to protect them from self‐stigma (Tsai et al, 2019). We also found that women who chose mastectomy without reconstruction reported significantly higher levels of self‐stigma than those who chose breast conservative surgery.…”
Section: Discussioncontrasting
confidence: 60%
“…Chinese immigrants adapted and adjusted to mainstream American culture, they received social support such as the Pink Ribbon campaign to protect them from self-stigma (Tsai et al, 2019). We also found that women who chose mastectomy without reconstruction reported significantly higher levels of self-stigma than those who chose breast conservative surgery.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, they did not want to burden their family caregivers, and some patients felt psychological distress was untreatable. They felt they could not benefit from talking about their distressing problems with caregivers, or they were ashamed to disclose their negative emotions because of disease sigma (Tsai et al, 2019). Family caregivers need to perform caregiving tasks and balance obligations at work (Yeung et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Women with breast cancer described the burden of being expected to be positive despite the continued association of cancer with death and how they sometimes had to downplay their private suffering to present a positive front to others [ 72 ]. Amongst these women, being less educated and opting for breast conservation surgery [ 71 ], being on chemotherapy, having depressive symptoms with high levels of ambivalence over emotional expression and intrusive thoughts [ 74 ] were significantly associated with higher self-stigma. Furthermore, there was significant inverse relationship between annual household income [ 74 ] and time since diagnosis 100] with self-stigma in patients with breast cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Amongst these women, being less educated and opting for breast conservation surgery [ 71 ], being on chemotherapy, having depressive symptoms with high levels of ambivalence over emotional expression and intrusive thoughts [ 74 ] were significantly associated with higher self-stigma. Furthermore, there was significant inverse relationship between annual household income [ 74 ] and time since diagnosis 100] with self-stigma in patients with breast cancer. Patients with breast and prostate cancers appeared less stigmatised [ 18 , 22 , 55 , 86 , 87 ].…”
Section: Methodsmentioning
confidence: 99%